PEDAGOGICAL SIMULATION OF THE PROFESSIONAL COMPETENCE FORMATION PROCESS IN THE MASTERS OF HUMANITIES - Dudka, Tetiana; Hrebeniuk, Viacheslav (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article considers the theoretical and practical significance of pedagogical modeling as an effective tool on the way to the formation of professional competence in the masters of humanities. The necessity of implementing Western standards into the national educational preparation for European integration perspectives of pro-Ukrainian development has been outlined. The purpose of the research is to outline the significance of the influence of pedagogical modeling tools on the professional competence formation process in the masters of humanities. The research purpose is focused on the need for a theoretical representation of the significance of the several external and internal factors that influence the subject, which can be effectively investigated using the method of pedagogical modeling The main characteristics of pedagogical modeling are visualized, which contributed to empathizing with the significance of the influence of information and communication technologies (ICT) on facilitating the perception of educational material by the subjects of cognition. The algorithm of phenomenological formation is outlined through two-level elements represented in the section of the implemented model. The research procedure was based on a combination of scientific methods of analysis and synthesis, induction and deduction, systematization, and generalization. With the help of such a methodological toolkit, it was possible to carry out a theoretical reproduction of the researched material in terms of substantiating the significance of the main stages of the pedagogical modeling implementation. The result of the research was the delineation of cognitive, reflexive, activity, and motivational structural components of professional competence by substantiating the significance of each of them at the level of phenomenological formation. The conclusions problematize the significance of pedagogical modeling actualizing theoretical and applied aspects of research, which contributes to the reproduction of phenomenological integrity through the unity of the relationships of each element of the system declared by the study. It has been concluded that the effectiveness of pedagogical modeling is significantly influenced by the productivity of subject reflection aimed at achieving the initial results of the research